Cyber Counseling Kesehatan Reproduksi bagi Remaja di Youth Center Griya Muda - Fatmala Eva Saroh; Mahmudah Mahmudah; Hasyim Hasanah (Nur Science Institute and Perkumpulan Keluarga Berencana Indonesia (PKBI) Semarang, 2022)
Background: Cyber ​​counseling is an innovative counseling service model. This study aims to determine the implementation of cyber counseling for adolescents at the PKBI Griya Muda Youth Center in Semarang City. Method: This type of research is descriptive qualitative research. Data collection techniques were carried out by interviews and documentation. The data analysis used follows the analysis of the Miles and Huberman models, namely data reduction, data presentation and verification. Result: The results of this study indicate that: first, the problems experienced by adolescents in cyber counseling at the Griya include problems in adolescent romance, sexual problems/premarital sexual behavior, pornography addiction problems, and reproductive health problems. Second, the implementation of cyber counseling which is carried out at the Griya Muda is one of the programs that provides counseling services via the internet or telephone for teenagers who want to consult their problems without having to meet a counselor in person. The implementation of cyber counseling consists of adolescent counselors, adolescent problems, methods and media used in the counseling process. The implementation of cyber counseling for teenagers at the Griya Muda is said to be successful, seeing from the decrease in client anxiety and the presence of clear goals for the future. Implication: For Griya Muda counselors it is recommended to (a) Improve cyber counseling services with a more focused work program (b) Improve administrative files related to the cyber counseling process that has been carried out